Monotheism and Christology in Greco-Roman Antiquity - Novenson, Matthew V., (Novum Testamentum, Supplements ;, 2021)
In Monotheism and Christology in Greco-Roman Antiquity , Matthew V. Novenson brings together thirteen state-of-the-art essays by leading scholars on the various ways ancient Jewish, Christian, and classical writers conceive of God, Christ, Wisdom, the demiurge, angels, foreign gods, and other divine beings. In particular, the book revisits the "early high Christology" debates of the 1990s, identifying the lasting contributions thereof as well as the lingering difficulties and new, emerging questions from the last thirty years of research. The essays in this book probe the much-touted but under-theorized distinctions between monotheism and polytheism, Judaism and Hellenism, Christianity and paganism. They show how what we call monotheism and Christology fit within the Greco-Roman world of which they are part.